Penerapan Buku Bergambar Sebagai Media untuk Meningkatkan Penguasaan Kosakata Bahasa Inggris pada Siswa Sekolah Dasar di Jakarta - Mas Idris; Lubna Himmatul Aini Luluatul (Journal of Science and Social Development, 2026)
This study examines a common problem faced by elementary school students: the limited mastery of English vocabulary, which often hinders their ability to understand and communicate effectively. Many students struggle to remember new vocabulary when learning through traditional methods that lack engaging visual elements. The purpose of this research is to determine the effectiveness of using illustrated books in improving elementary students’ English vocabulary mastery. A total of 20 students participated in the study, which employed a pre-test–post-test design. Before the treatment, students took a pre-test to measure their initial vocabulary ability, with an average score of 18%. Then, the students received instruction using illustrated books that presented the target vocabulary through pictures. After the intervention, a post-test was conducted to assess improvement. The results showed a significant increase in vocabulary scores, from 18% to 82%. These findings indicate that illustrated books provide strong visual support and contextual cues that enhance students’ understanding and retention of new vocabulary. Therefore, the use of illustrated books is proven effective in improving elementary students’ vocabulary mastery while making the process of learning English more engaging, memorable, and enjoyable.